Educação alimentar e nutricional: uma análise histórico-crítica da relação educação, alimentação e nutrição - Moreau, Luiza Pompeu Prado Moreira (Universidade Federal de São Carlos, 2021)
This dissertation seeks to present a historical analysis of the process of genesis and development of Food and Nutrition Education (EAN) in Brazil, seeking to understand the concepts of food, nutrition and education present in the area's initiatives and policies and the historical-social meaning pointed out by them. For this, we used bibliographical research and documental analysis, emphasizing the historical analysis and critical reflection of the elements present in the analyzed context. EAN aims to study and disseminate information on adequate and healthy eating and promote healthy eating habits through public policies based on educational resources. The scenario observed within EAN's initiatives and policies indicates the need to expand the debate around the theoretical-methodological bases that underlie its approach, as this still occurs in a fragmented, isolated and decontextualized way from the historical-social reality. In our analysis, we seek to consider the concrete determinants that permeate the development of EAN, that is, the struggles and contradictions present in capitalist society. For that, we believe that the Historical-Critical Pedagogy, and its orientation from the Historical-Dialectical Materialism, are presented as fundamental for the analysis of this context. In our analysis, we present the periodization of the formation of food and nutrition policies in three historical moments: 1940-1970: period characterized by the development of dissemination instruments on healthy eating, with the aim of correcting erroneous eating habits and presenting the pillars of rational food; 1970-1990: period characterized by the valorization of the income-food binomial and by a critique of EAN policies, in this period food supplementation and food distribution policies prevail; 1990-present: period characterized by the discussion of food as a human right, coexisting income access and EAN policies. There has been an expansion of the EAN concept over time, added to an expansion of social rights. Food came to be understood as a human right and a duty of the State, nutrition was no longer seen from a strictly technical and biological point of view, but also considered cultural issues. The concept of hegemonic education has undergone changes, but remains always within the framework of a non-critical view, placing education as a redeemer of social problems. In the end, we observe that due to the development of initiatives and policies within the capitalist logic, successive political-economic crises have set back the few advances obtained. and with that, the conquests that had been hard won were lost with the characteristic instability of this economic system. Therefore, we reiterate the importance of discussing the theoretical foundations that guide the EAN and the development of a critical EAN that can effectively contribute to the training, health, food, nutrition and emancipation of the working class. In this way, we consider the contributions of PHC to be fundamental in the sense of thinking about a new praxis for EAN.
Food and nutrition education: a historical-critical analysis of the relationship between education, food and nutrition
Keywords: Educação alimentar e nutricional; Pedagogia histórico-crítica; Educação em saúde; Food and nutrition education; Historical-Critical Pedagogy; Health education; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS; CIENCIAS DA SAUDE::NUTRICAO; CIENCIAS DA SAUDE::SAUDE COLETIVA; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO::HISTORIA DA EDUCACAO; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA